Evaluation of the Contribution Rates of Different Phases on Pavement Performance of Cement-Casting Asphalt Mixture - Minghui Gong; Zijia Xiong; Lei Jiang; Cheng Deng; Sheng Li; Jinxiang Hong (Advances in Materials Science and Engineering)
Cement-casting asphalt mixture (CCAM) exhibits excellent antirutting properties and has been widely used to address the severe rutting distress across the world. However, CCAM’s failure mechanism has not been comprehensively understood. To this end, the contribution rates of porous asphalt mixture (PAM), cementitious network, and asphalt-cement interface phases to CCAM’s pavement performance are evaluated. A novel method was developed to fabricate the cementitious network with the aid of plastic balls. Abrasion loss, strength, peak force, and fracture energy of PAM, cement samples, and CCAM samples are obtained through different tests. Analysis results show that the contribution rate of cementitious network to Cantabro loss is around 60% and that of the interface phase is around 30%. Interface phase and PAM phase approximately contribute 90% to the overall strength and fracture energy of CCAM. With the increase of polymer contents in asphalt binder, the contribution rate of PAM phase increases and the contribution rate of interface decreases. Contribution rates results together with samples’ fracture surface observation verify that the interaction between asphalt skeleton and cement network plays a vital role during CCAM’s failure process. Attention should be given to the physical-chemical interactions between asphalt and cement in the future study.